Expanding Access to Early Childhood Development Using Interactive Audio Instruction : Guidelines for Program Design and Reportback on Prototyping in the Democratic Republic of Congo - World Bank (World Bank, Washington, DC, 2015)
A large body of solid evidence demonstrates the significant effects of early childhood education and development (ECED) interventions on children’s success in school, long-term social integration, and improved life chances. Interactive audio instruction (IAI) provides one solution to the challenge of providing high quality ECE at scale and at reasonable costs. The IAI medium allows for the development and delivery of both teacher and caregiver training and direct instruction, using best practices in ECE, and has demonstrated powerful results in contexts as diverse as Honduras, Nepal, El Salvador, Indonesia, Zanzibar, Malawi, and Paraguay. The document outlines a general approach to high-quality IAI production for ECD, and uses the Democratic Republic of Congo (DRC) case study to detail the development process. It also provides technical recommendations for how to scale-up production and delivery in the DRC and considerations for program adaptation in other similar contexts, including an outline of necessary steps and components, estimated costs of a program with broad reach and content depth (including a financial model for production and program implementation), and a results monitoring and evaluation framework. The attached report is divided into two parts. Part one outlines the process for scaling up an IAI program - from initial start-up in a given community, to large scale expansion in a country. It highlights the main steps in the production cycle, the roles and responsibilities of government and communities, and provides useful tips for practitioners at each stage of the process. Part two provides a summary of how this process was followed in DRC and lessons learned.